Civil Society and Gender Mainstreaming: Case Study of the Working Group on Women and Preventing/Countering Violent Extremism (WGWC) Program - Zuhri, Saefudin; Mustain Mashud; Daniel T. Sparingga (JURNAL PENELITIAN, 2023)
The transformation of women's role in terrorism networks from victims to supporters, perpetrators and even recruiters as well as ideologues is now a social phenomenon in Indonesia. Civil society organizations (CSOs) responded to this phenomenon by forming the Working Group on Women and Preventing/Countering Violent Extremism (WGWC). There are several reasons behind this movement, such as; the strong patriarchal culture and regime in society and policy makers, the lack of women's involvement in efforts to eradicate violent extremism and terrorism, and the sporadic work of CSOs. This research uses a qualitative methodology with a case study approach. Data and information were obtained from interviews and documentation. The research found several points. First, WGWC be a forum for activists, academics, and civil society organizations in Indonesia on gender mainstreaming and countering violent extremism in Indonesia issues. WGWC applies a collegial collective system by sharing the framework of civil society partners. WGWC works voluntarily, independently and autonomously. Second, WGWC acts as a critical and strategic partner of the government in gender mainstreaming by intervening in policies and programs of the National Action Plan for Preventing and Countering Violent Extremism that Leads to Violence (RAN PE) and Regional Action Plans (RAD PE).